An electrochemical DNA biosensor based gold-thiolate conjugation utilizing ruthenium complex [Ru(dppz)2(qtpy)]Cl2 - Foo, K.L.; Muhammad Fayyaz, Kashif; Tan, S.J.; Hashim, U. (Springer Verlag, 2017)
Non toxicity and high isoelectric point of zinc oxide nanorods (ZnO NRs) are the promising materials widely used in biomolecule detection and biomedicine application. An electrochemical DNA biosensor was successfully fabricated by depositing (3-Aminopropyl)triethoxysilane and gold nanoparticles (GNPs) on the hydrothermal growth ZnO NRs. The modified surface with GNPs (35 ± 5 nm) was characterized by field emission scanning electron microscopy with energy dispersive X-ray and X-ray diffraction. The fabricated electrode was used for the label-free detection of DNA. Thiolated (–SH) single stranded DNA was immobilized onto the GNPs surface to form a gold-thiolate bond. Hybridization with complementary target DNA was performed with the presence of ruthenium complex. Immobilization and hybridization detection were performed using µAUTOLAB with cyclic voltammetric software. The measured sensitivity of the fabricated electrode for hybridization is up to 1.6 times larger than immobilization. © 2016, Springer-Verlag Berlin Heidelberg.